Solvent Effects on the Ultraviolet Absorption of Polystyrene - Story, V. M. (J Res Natl Bur Stand A Phys Chem, 1967)
NBS Standard Sample Polystyrene 705 is shown to exhibit a small, but significant, hypochromism in the 38,300 cm(−1) region in several solvents compared to the model compound, ethylbenzene. Beer’s law is not obeyed for solutions of the polymer in all solvents. The concentration dependence of the extinction coefficient is related to the scattered light and its dependence on the activity coefficient of the solvent. The specific extinction coefficients for polystyrene 705 in cyclohexane and in carbon tetrachloride are 20.89 and 27.38, respectively.